Football, Media, and Homophobia: Public Framing of the First Pride Game in the Australian Football League. (August 2020) - Sherwood, Merryn; Donaldson, Alex; Dyson, Suzanne; Lowden, David; Marjoribanks, Timothy; Shill, Jane; Bolam, Bruce; Nicholson, Matthew
Two Australian football clubs—St Kilda and the Sydney Swans—played the first Pride Game in Australian professional sport in 2016 to support and include the lesbian, gay, bisexual, transgender, intersex, and queer (LGBTIQ) community at and through a major sporting event. This study examines the framing of this game in the print and online media and in public responses via comments on media coverage and comments on Facebook posts. The framing of both the media coverage and the public response was predominantly supportive, with the theme of the "inclusion, " of gay Australian Football League players and the broader LGBTIQ community, prominent. However, there was a significant difference in the frames used in media coverage compared to the public response to this coverage. There was a relatively high proportion of unsupportive comments (e.g., a "stick to football" theme), including pernicious homophobia, present, particularly in the public response, compared to other recent related research. Overall, the findings suggest that, while there was strong support for the Pride Game, homophobia in sport remains, and the media, particularly social media, can be a platform for its expression. This study also highlights the value in analysing multiple platforms in media framing research.